1980
DOI: 10.1021/bi00563a017
|View full text |Cite
|
Sign up to set email alerts
|

Conformational dynamics of insulin in solution. Circular dichroic studies

Abstract: Conformational changes of bovine insulin in solution with concentration and pH detected by circular dichroic (CD) studies are reported. The change in the CD spectrum of insulin in the higher concentration range (from 100 microM down to 2 microM) is relatively small, but in the lower concentration range (from 2 microM down to 60 nM) the CD spectrum changes substantially with concentration. A detailed analysis of the data indicates that the hormone has two major conformational states: conformation I, a form whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 21 publications
8
82
0
Order By: Relevance
“…35 Therefore, it was employed as an easy tool to study the conformational stability of the rhINS. Preparative variables, such as homogenization pressure and number of cycles, hydration time, amount of soybean phosphotidylcholine and insulin, and volume of organic solvents volume, at their extreme levels, may have an impact on the conformational stability of rhINS.…”
Section: Conformational and Bioactive Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…35 Therefore, it was employed as an easy tool to study the conformational stability of the rhINS. Preparative variables, such as homogenization pressure and number of cycles, hydration time, amount of soybean phosphotidylcholine and insulin, and volume of organic solvents volume, at their extreme levels, may have an impact on the conformational stability of rhINS.…”
Section: Conformational and Bioactive Stabilitymentioning
confidence: 99%
“…35,36 The ratio of θ 208 /θ 223 can be used as a qualitative measure of rhINS association. 34 This is due to the antiparallel β structure which forms when two monomers dimerize.…”
Section: Conformational and Bioactive Stabilitymentioning
confidence: 99%
“…It has been assumed that the hormone's structure does not change significantly when it dimerizes but it is difficult to prove this unequivocally. Indeed, spectroscopic studies have suggested that the insulin monomer partially unwinds in solution (Pocker & Biswas, 1980), which would invalidate the structure-function arguments (Blundell, Dodson, Hodgkin & Mercola, 1972;Peking Insulin Structure Research Group, 1974). However, the crystal structure of DPI shows that this modified monomer is closely similar to the insulin structure present in 2-Zn insulin and in the dimer forms of hagfish insulin and pig insulin (Cutfield, Cutfield, Dodson, Dodson, Reynolds & Vallely, 1981;Dodson, Dodson, Hodgkin & Reynolds, 1979).…”
Section: Discussion (1) Methodsmentioning
confidence: 99%
“…Generally, the secondary structures (α-helix and β-fold) can illustrate the efficacy of insulin, and CD is regarded as one of the most effective methods to evaluate the secondary structures of proteins and peptides. 27 Figure 4 shows the CD spectra of the insulin secondary structures. The CD spectra of insulin in mixture with emulsion and the coated nanoemulsion were totally identical to the insulin solution, which showed a peak valley at 209 nm and a shoulder at around 225 nm.…”
Section: Conformational Stability Of Insulinmentioning
confidence: 99%